The Development and Validation of a High-Performance Liquid Chromatographic Method for the Determination of Urinary Levels of Etoricoxib After Fabric Phase Sorptive Extraction - Anastasia Korpeti; Natalia Manousi; Abuzar Kabir; Constantinos K. Zacharis; Erwin Rosenberg (Separations)
Herein, a simple and effective analytical method was developed to monitor etoricoxib concentrations in human urine samples. Etoricoxib is a nonsteroidal anti-inflammatory drug for pain and inflammation relief in conditions such as osteoarthritis and rheumatoid arthritis. To determine its concentration, fabric phase sorptive extraction (FPSE) was combined with high-performance liquid chromatography and diode array detection (HPLC-DAD). FPSE is a green sample preparation technique that utilizes sol–gel-coated fabric substrates as extraction devices, offering numerous benefits in bioanalysis. Initially, different materials were tested for their affinity towards etoricoxib. The most critical FPSE parameters (i.e., sample amount, stirring rate, and adsorption time) were optimized using a face-centered central composite design (FC-CCD), while the remaining ones were explored by means of the one-variable-at-a-time approach. Afterwards, the analytical method was validated in terms of its selectivity, linearity, sensitivity, accuracy, and precision, while the environmental sustainability and the practicality of the method were also examined. The limit of detection was 0.03 μg mL−1, and the lower limit of quantification was 0.10 μg mL−1. The relative standard deviation was less than 7.2% in all cases, showing good precision. The proposed approach was successfully used to monitor urinary etoricoxib concentrations in real samples obtained from a volunteer after oral drug administration.